Association of Reported Trimester-Specific Smoking Cessation With Fetal Growth Restriction. Issue 6 (June 2015) - Blatt, Kaitlin; Moore, Elizabeth; Chen, Aimin; Van Hook, James; DeFranco, Emily A.
Abstract : OBJECTIVE: To assess the association of reported smoking cessation at various time points during pregnancy with fetal growth restriction. METHODS: This was a population-based retrospective cohort study of singleton nonanomalous live births using Ohio birth certificates, 2006–2012. Outcomes of women who reported smoking only in the 3 months before conception and women who reported smoking through the first, second, or third trimester were compared with a referent group of nonsmokers. Multivariate logistic regression assessed the association between smoking cessation at various times in pregnancy and fetal growth restriction less than the 10th and 5th percentiles. RESULTS: Of 927, 424 births analyzed, 75% of mothers did not smoke. Of smokers, 24% smoked preconception only, 10% quit after the first trimester, 4% quit after the second trimester, and 59% smoked throughout pregnancy. The rate of fetal growth restriction less than the 10th and 5th percentiles among nonsmokers was 8.1% and 3.6%, respectively. Although smoking only in the preconception period did not significantly increase fetal growth restriction risk, smoking in any trimester did. The adjusted odds ratio (95% confidence interval) for fetal growth restriction less than the 10th and 5th percentiles, respectively, of cessation after the first trimester was 1.19 (1.13–1.24) and 1.25 (1.17–1.33) and 1.67 (1.57–1.78) and 1.83 (1.68, 1.99) for cessation after the second trimester. Women who reported smoking throughout pregnancy had the highest risks of fetal growth restriction, 2.26 (2.22–2.31) and 2.44 (2.37–2.51), after accounting for the influence of race, low socioeconomic status, and medical comorbidities. CONCLUSION: Smoking of any duration during pregnancy is associated with an increased risk of fetal growth restriction with decreasing risk the earlier that cessation occurs. Smoking cessation programs should focus on the benefit of quitting as early in pregnancy as possible. LEVEL OF EVIDENCE: II Abstract : Smoking during any trimester is associated with an increased risk of fetal growth restriction.